Neutrophil gelatinase‐associated lipocalin (NGAL) levels in response to unilateral renal ischaemia in a novel pilot two‐kidney porcine model. (19th March 2013) - Silberstein, Jonathan L.; Sprenkle, Preston C.; Su, Daniel; Power, Nicholas E.; Tarin, Tatum V.; Ezell, Paula; Sjoberg, Daniel D.; Feifer, Andrew; Fleisher, Martin; Russo, Paul; Touijer, Karim A.
Abstract : Objectives: To test a novel porcine two‐kidney model for evaluating the effect of controlled acute kidney injury (AKI) related to induced unilateral ischaemia on both renal units (RUs) To use neutrophil gelatinase‐associated lipocalin (NGAL) and physiological serum and urinary markers to assess AKI and renal function. Methods: Twelve female Yorkshire pigs had bilateral cutaneous ureterostomies placed laparoscopically with identical duration of pneumoperitoneum for all cases. An experimental group ( n = 9) underwent induced unilateral renal ischaemia with left hilar clamping of timed duration (15, 30, 60 min) and a control group ( n = 3) had no induced renal ischaemia. Urine was collected and analysed from each RU to assess creatinine and NGAL concentration preoperatively and at multiple postoperative time points. Serum was collected and analysed daily for creatinine and NGAL levels. Statistical comparisons were made using the rank‐sum and sign‐rank tests. Results: Three pigs were excluded because of intra‐operative and postoperative complications. In the RUs that experienced renal ischaemia ( n = 7), the median urine volume was lower ( P = 0.04) at 6, 12, 24 and 48 h and the median NGAL concentration was higher ( P = 0.04) at 12 and 48 h compared with the RUs of control pigs that experienced no renal ischaemia ( n = 2). When comparing the ischaemic (left) RU of the pigs in the experimental group with their contralateral non‐ischaemic (right) RU, ischaemic RUs had a lower median cumulative urine volume at 6, 12, 24 and 48 h ( P = 0.05) and a higher median NGAL concentration at 12, 24 and 48 h ( P < 0.05). At 48 h, no significant increase was found in serum NGAL in pigs in the experimental group compared with controls ( P = 0.2). Creatinine clearance (CC) was lower in ischaemic RUs compared with non‐ischaemic RUs 1 day after surgery ( P = 0.04) with decreasing CC as the duration of ischaemia increased. Conclusions: We have developed a promising novel small‐scale pilot surgical model that allowed the evaluation of bilateral RU function separately during and after unilateral renal ischaemia. The induction of unilateral renal ischaemia corresponds with physiological changes in both the ischaemic and contralateral RU. AKI as measured by increases in NGAL and decreased renal function as measured by decreases in CC, are specific to the RU exposed to ischaemia.